Zagrożenie zawodowe anestezjologów w dobie pandemii COVID-19 - Wujtewicz, Magdalena; Dylczyk-Sommer, Anna; Aszkiełowicz, Aleksander; Stefaniak, Jan; Zdanowski, Szymon; Owczuk, Radoslaw (Anestezjologia Intensywna Terapia, 2020)
According to the Occupational Safety and Health Administration of the Department of Labor of the United States, the exposure risk for anaesthesiologists working with COVID-19 patients can be classified as high or very high. This is mostly due to fact that the anaesthesiologists work in close contact with patients’ airways, and the aerosol-generating nature of some procedures they perform. Fortunately, despite the occupational hazard, the incidence of COVID-19 among anaesthesiologists and intensivists remains relatively low. Current evidence suggests that the majority of SARS-CoV-2 infections in this group were either contracted outside of the work environment or can be attributed to personal protective equipment (PPE) malfunction. This article focuses on different aspects of anaesthesiologists’ safety, risks connected with different clinical scenarios and procedures, issues related to testing and screening, as well as modifiable and non-modifiable risk factors for severe illness or from COVID-19. This analysis is accompanied by a review of guidelines dedicated to mitigating said risks. Educating the personnel, introducing appropriate procedures, and proper utilisation of PPE are essential to the safety of all parties involved in hospital care, particularly those with significant exposure risk.